Spatial and temporal variability in energy and water vapour fluxes observed at seven sites on the Indian subcontinent during 2017. (3rd December 2019) - Bhat, G. S.; Morrison, R.; Taylor, C. M.; Bhattacharya, B. K.; Paleri, S.; Desai, D.; Evans, J. G.; Pattnaik, S.; Sekhar, M.; Nigam, R.; Sattar, A.; Angadi, S. S.; et al.
Abstract: Under the INCOMPASS project, state of the art eddy‐covariance based surface flux measurement systems were installed at eight locations across India. These sites cover different climatic conditions, land use and land cover, and water management practices. Here we present the initial analysis of the measurements taken at seven sites mainly focusing on the year 2017, quantifying for the first time the remarkable contrasts in evaporative fraction across the seasons, climate zones and land management practices of the Indian subcontinent. With the exception of Jaisalmer which is the driest of the places studied, all the sites maintain values of evaporative fraction above 0.5 after the monsoon through to November. By contrast, for those sites with natural vegetation or rain‐fed agriculture, evaporative fraction remains below 0.3 for the dry January–May period. In the middle Gangetic Plain area, irrigation and pre‐monsoon showers together maintain evaporative fraction above 0.5 between January and June. It is also observed that different variables exhibit different intraseasonal variation characteristics even at one site. Except for Samastipur which is situated in the middle Indo‐Gangetic Plains, wind speed shows spectral peak at a smaller time‐scale compared to sensible and latent heat fluxes. Abstract : This study heralds a step change in land surface observations in India with the first‐time measurement of evaporative fraction across the country using state‐of‐the‐art instruments and covering all seasons, a range of surface and climate conditions. The panels show monthly variation of (a) turbulent heat flux, (b) evaporative fraction, and (c) CO2 flux at BLR – Bengaluru, BBS – Bhubaneswar, DWR – Dharwad, JSM – Jaisalmer, KNP – Kanpur, NWG – Nawagam and SMS – Samastipur. The panels bring out the complexity that exists across India.